PERAN MASYARAKAT DI DESTINASI WISATA PANTAI KONENG DUMAI, KECAMATAN MEDANG KAMPAI KOTA DUMAI - Utami, Lestari Dian; Yusrizal, Firdaus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Koneng Beach is one of the seaside tourist destinations in Medang Kampai District, Dumai City. An area that faces directly with Malaysia with attractive aquatic tourism potential. Starting in 2017, Koneng Beach has been successfully visited by thousands of visitors. This research was conducted in the Koneng Dumai Beach Tourist Destination, Medang Kampai District, Dumai City, this research aims to find out the Role of the Community in Koneng Beach Tourist Destination. The research method that will be used in this study is Qualitative with the type of Grounded Research. Data collection was carried out by observation and interview methods by interviewing several local people living around Koneng Beach. Through interviews conducted with 4 Informants, it was found that 3 roles of the community in the Koneng Dumai Beach tourist destination are: 1) Tourism Services, 2) Environmental Conservation, 3) Field Officer. Keywords: the role of the community in beach tourism destinations